MONITORING LOG SERVER DENGAN ELASTICSEARCH, LOGSTASH DAN KIBANA (ELK) - Aviecenna Yudhistira; Yuli Fitrisia (LPPM Universitas Abdurrab, 2023)
The use of servers that have to run continuously for 24 hours and running services generates a lot of logs. This requires that the system administrator in his checks still have something to do with the server. This research intends to design a Monitoring Log Server using the ELK Stack (Elasticsearch Logstash Kibana) which can make it easier to read and analyze service logs on the server. The implementation in this research uses Ubuntu 18.04 Server, and a client server with SSH Putty service. From the results of the ELK Stack research, a solution in the form of Monitoring Log Server is obtained to make it easier for administrators to check every access log. Based on the results of the first and second scenario testing, the results obtained are successful in displaying data for each log that can be read by the administrator for a period of time based on data per day and per week. For the third scenario the administrator can see the level of accuracy of each access log. And the last scenario is the result to make it easier for administrators to audit or check every access log.